Disorder in the composite crystal structure of the manganese `disilicide' MnSi1.73 from powder X‐ray diffraction data. Issue 6 (1st December 2015) - Akselrud, L.; Cardoso Gil, R.; Wagner‐Reetz, M.; Grin, Yu.
Abstract : The crystal structure of the higher manganese silicide MnSi1.7 (known in the literature as HMS) is investigated in samples with different compositions obtained by different techniques at temperatures not higher than 1273 K. Powder X‐ray diffraction was applied. The crystal structure is described as incommensurate composite. In addition to the ordered model already known in the literature, the partial disorder in the silicon substructure was detected and described introducing an additional atomic site with a different modulation function.